GOOGLE TRANSLATE AS AN ALTERNATIVE TOOL FOR ASSISTING STUDENTS IN DOING TRANSLATION : A CASE STUDY AT UNIVERSITAS NEGERI JAKARTA, INDONESIA - Ninin Herlina; Ratna Dewanti; Ninuk Lustiyantie (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2019)
Abstract The paper examines the use of Google Translate as an Alternative tool for assisting students at Universitas Negeri Jakarta, Indonesia to translate and develop their knowledge and skills in doing Translation. The participants of the study were 36 students at the Applied Linguistic of Doctoral Program at Universitas Negeri Jakarta who had registered of the year 2017. Based on literature review, analysis of the collecting data, and an assessment of the course content and activities inside and outside the learning process, the findings suggest that most Applied Linguistic of Doctoral Program students at Universitas Negeri Jakarta recognize Google Translate as an Alternative tool for doing references book translation. In fact, some students reported that they could optimally ,benefit from self-learning if they were assisted to use Google Translate effectively. Moreover, using Google Translate for doing classroom tasks and reference books translation encourage students to study independently, and to shape their own strategies for solving language problem. Keywords : Google Translate, Alternative Tool, Translation, Assisting Student